Influência do excesso de informações na vulnerabilidade do consumidor e em sua disposição a pagar - Martinez, João Roberto Lo Turco (2012)
This study aims to understand and test the relation between information overload confusion, consumer vulnerability and willingness to pay. For this, first I developed a consumer vulnerability scale based on coping strategies resulting of vulnerability (disattaching, distancing and fantasy). Then, it was realized an experiment, in which I manipulated the quantity of information and the vital information obtaining so randomly four groups (confused with vital information, confused without vital information, not confused with vital information and not confused without vital information). After that, I measured the willingness to pay and the vulnerability score of the groups. As main results I conclude that the confused consumer has a higher willingness to pay in relation to the not confused consumer, and that the confused consumer that received the vital information has higher willingness to pay than the confused consumer that not received and also than the not confused consumer. Another conclusion is that consumers in confusion state has higher vulnerability score than the not confused one and that the vulnerability is a mediator of the relation between confusion and willingness to pay.